Cone beam computed tomography images fusion in predicting lung ablation volumes: a feasibility study. (February 2016) - Ierardi, Anna Maria; Petrillo, Mario; Xhepa, Genti; Laganà, Domenico; Piacentino, Filippo; Floridi, Chiara; Duka, Ejona; Fugazzola, Carlo; Carrafiello, Gianpaolo
Background: Recently different software with the ability to plan ablation volumes have been developed in order to minimize the number of attempts of positioning electrodes and to improve a safe overall tumor coverage. Purpose: To assess the feasibility of three-dimensional cone beam computed tomography (3D CBCT) fusion imaging with "virtual probe" positioning, to predict ablation volume in lung tumors treated percutaneously. Material and Methods: Pre-procedural computed tomography contrast-enhanced scans (CECT) were merged with a CBCT volume obtained to plan the ablation. An offline tumor segmentation was performed to determine the number of antennae and their positioning within the tumor. The volume of ablation obtained, evaluated on CECT performed after 1 month, was compared with the pre-procedural predicted one. Feasibility was assessed on the basis of accuracy evaluation (visual evaluation [VE] and quantitative evaluation [QE]), technical success (TS), and technical effectiveness (TE). Results: Seven of the patients with lung tumor treated by percutaneous thermal ablation were selected and treated on the basis of the 3D CBCT fusion imaging. In all cases the volume of ablation predicted was in accordance with that obtained. The difference in volume between predicted ablation volumes and obtained ones on CECT at 1 month was 1.8 cm 3 (SD ± 2, min. 0.4, max. 0.9) for MW and 0.9 cm 3 (SD ± 1.1, min. 0.1, max. 0.7) for RF. Conclusion: Use of pre-procedural 3D CBCT fusion imaging could be useful to define expected ablation volumes. However, more patients are needed to ensure stronger evidence.